Programe of the “Second Creation” of Man in the Philosophy of Oxford’s Reformers - Urbonavičius, A. (Problemos, 1995)
The paper deals with the development of Renaissance thought in England. The views of John Colet, Erasmus, and Thomas More are considered. The unity of views of Christian humanitarians was determined by common problems as well as by the common structure of thinking. It is demonstrated how John Colet makes out his programme of the active “ennoblement” of man by founding his neoplatonic cosmology. The programme contained within itself all trends that were developed later by Erasmus and More.